2021
DOI: 10.25077/jom.6.2.12-22.2021
|View full text |Cite
|
Sign up to set email alerts
|

Does Cesarean Section Increase the Risk of Postpartum Depression? A Systematic Literature Review

Abstract: Background: Postpartum depression (PPD) is a psychological disorder experienced by mothers at 4 weeks to 6 months postpartum. One of the risk factors for postpartum depression is the type of delivery. The mode of delivery in its effect on postpartum depression has been studied extensively with conflicting results whether vaginal delivery or cesarean section (CS) that can affect postpartum depression (Rauh et al., 2012). Methods: This is a systematic literature review with a research question using PICO standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Systematic reviews have reported that the mode of delivery is associated with depressive symptomatology, speci cally after a cesarean section [29]. The level of stress before the surgical procedure, along with the pain experienced throughout and after an ECD, is more likely to cause depressive symptoms in an early postoperative stage [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews have reported that the mode of delivery is associated with depressive symptomatology, speci cally after a cesarean section [29]. The level of stress before the surgical procedure, along with the pain experienced throughout and after an ECD, is more likely to cause depressive symptoms in an early postoperative stage [30,31].…”
Section: Discussionmentioning
confidence: 99%